2012
DOI: 10.21608/jpp.2012.84211
|View full text |Cite
|
Sign up to set email alerts
|

Integration Effects of Mulching and Burning With Hoeing on Sugar Beet and Associated Weeds.

Abstract: Two field experiments were carried out during 2008/2009 and 2009/2010 winter seasons to evaluate the effect of some non-traditional methods for weed control which are being (mulching by rice straw and burning has been carried after ridging and directly before sowing) on growth, yield and juice quality as well as associated weeds of sugar beet (Beta vulgaris, L.) grown in salinity soil condition at El-Serw Research Station. The most important results obtained could be summarized as follows:-All weed control tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In this respect, Abo El-Hassan (2010) found that root length, root diameter, root weight, top fresh weight, top yield, root yield and sugar yield of sugar beet were significantly affected by weed control treatments. Also, Tagour et al (2012) found that hand hoeing twice with mulching gave the highest values of tops, roots, biological and sugar yields. May (2003) reported that sugar beet is a poor competitor with weeds in arable fields because it is slow growing early in the season and has a low canopy.…”
Section: Introductionmentioning
confidence: 95%
“…In this respect, Abo El-Hassan (2010) found that root length, root diameter, root weight, top fresh weight, top yield, root yield and sugar yield of sugar beet were significantly affected by weed control treatments. Also, Tagour et al (2012) found that hand hoeing twice with mulching gave the highest values of tops, roots, biological and sugar yields. May (2003) reported that sugar beet is a poor competitor with weeds in arable fields because it is slow growing early in the season and has a low canopy.…”
Section: Introductionmentioning
confidence: 95%